The rise and fall of Spanish unemployment: A chain reaction theory perspective - Marika Karanassou; Hector Sala (Queen Mary University of London, Department of Economics, 2008)
The evolution of Spanish unemployment has been quite idiosyncratic. The full-employment levels of the early seventies were followed by unemployment rates that were the highest within the OECD countries in the aftermath of the oil price shocks. While unemployment was extremely persistent in most of the eighties and nineties, it experienced its sharpest decline in recent years. We investigate the determinants of this unemployment trajectory using the analytical framework of the chain reaction theory (CRT). We show that unemployment may not gravitate towards its natural rate due to frictional growth, a phenomenon that arises from the interplay of lagged adjustment processes and growing exogenous variables in a dynamic system with spillovers. The empirical analysis distinguishes four periods: (i) 1978-1985, (ii) 1986-1990, (iii) 1991-1994, (iv) 1995-2005, and finds that capital accumulation is a crucial driving force of unemployment. Thus, our theoretical and empirical results question the key role of the natural rate in policy making.
Keywords: E22; E24; J21; 330; labour market dynamics; frictional growth; chain reaction theory; capital accumulation; impulse response function; Arbeitslosigkeit; Volatilität; Investition; Spanien